Juan Antonio Monroy An Autobiography - Monroy, Juan Antonio (Abilene Christian University Press, 2011)
Juan Antonio Monroy was a Marxist atheist as a young man, but since his conversion his passion has been to tell everyone he meets about Jesus. He has traveled to all of earth's continents except Antarctica and to many of the countries of those continents. He has experienced religious and political persecution and, as a result, helped found what became known as Amnesty International. Juan Antonio Monroy's footprints are seen around the world. His books, pamphlets, and articles are read in English and Spanish, and his radio programs are heard across Europe, the Caribbean, and much of Central and South America. In this long-awaited autobiography, he tells his fascinating story. • A militant atheist turned Christian evangelist • Baptized in Morocco, Africa, in 1950 by a Cuban missionary • Joined the Herald of Truth evangelistic team in 1964 • Presented his first radio broadcast in 1967 • In 1985, he became the first minister with Churches of Christ to enter Cuba since the revolution • He continues to travel and teach at a pace that belies his age